Mark of the beast : death and eegradation in the literature of the Great War - Bonadeo, Alfredo (University Press of Kentucky, 1989)
The First World War is a watershed in the intellectual and spiritual history of the modern world. On the one hand, it brought an end to a sense of optimism and decency bred by the prosperity of nineteenth-century Europe. On the other, it brought forth a sense of futility and alienation that has since pervaded European thought. That cataclysmic experience is richly reflected in the work of writers and artists from both sides of the conflict, and this study provides a detailed analysis of two basic themes -- death and degradation -- that mark the literature about the war.